A review of available methods and description of a new method for eliminating ectoparasites from bird nests. Issue 3 (27th August 2015) - Hund, Amanda K.; Blair, Jessica T.; Hund, Frederick W.
ABSTRACT: Bird nests offer an ideal situation to manipulate ectoparasites and study how they impact hosts. Several methods are available to eliminate parasites from nests and each has its own suite of advantages and disadvantages. For example, recent toxicity research has revealed that some commonly used insecticides may not be suitable for use in experiments with nestlings. This highlights the need for investigators to control for the effects of methods used to eliminate nest parasites within experimental designs. Methods that can be used across treatment groups are also often needed to study the effects of variation in parasite intensity. To aid investigators in deciding which method(s) to use, we provide a comprehensive review of available methods for eliminating nest ectoparasites and also describe a new heat gun method. We tested the effectiveness of the heat‐gun method with nests of Barn Swallows ( Hirundo rustica ) to which 100 nest mites were added and then quantified the number of surviving mites and other naturally occurring arthropods. We found that fully heated nests had significantly fewer mites and other arthropods than partially heated or control nests. Use of the heat gun had no negative effects on nestling growth or mortality rates. In studies of avian nest ectoparasites, investigators need to consider methods that can be used across treatment groups to ensure that unaccounted for toxicity effects are not influencing results and leading to underestimation of the often subtle effects of ectoparasites on birds.